Leaf sampling to assess mineral nutrient composition of physic nut plants (Jatropha curcas L.) - de Lima, Rosiane de Lourdes Silva; de Azevedo, Carlos Alberto Vieira; Gheyi, Hans Raj; Cazetta, Jairo Osvaldo [UNESP]; Carvalho, Genelicio Souza; Arrriel, Nair Helena de Castro (Southern Cross Publishing, 2016)
The physic nut is an important plant for biodiesel production. However, research is still lacking as to the best leaves to be sampled in determining ideal mineral content. It is important that all factors causing variations in the mineral nutrient concentrations in leaves are identified and evaluated to determine the most efficient sampling technique. The positions of the leaves on the branches and on the plant shoot are critical variables affecting leaf composition. Thus, this study aimed to determine the best leaf position for sampling to evaluate the health status of adult physic nut plants. The experiment was conducted in the field, using a 5 ï¿½ 3 factorial design, with leaves sampled at five positions on the branch (1st, 2nd, 3rd, 4th, and 5th node, from the apex), and three sections of the plant crown (apical, middle, and basal), in a completely randomized design with four replications, and four plants per plot. The concentration of macronutrients (N, P, Ca, Mg, and S) and micronutrients (Cu, Fe, Mn, and Zn) were determined for all samples. The results indicated that the sampling of leaves at the 3rd and 4th node of the flower-bearing branches, located in the middle section of the plant canopy, was the most indicative of the mineral composition of adult jatropha plants.
Keywords: Jatropha curcas; Leaf sampling; Mineral composition